Effect of Asymmetric Geometry on the Flexibility of Stent - Achmad Syaifudin; Ryo Takeda; Katsuhiko Sasaki (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2017)
Mechanical characteristic assessment of the new stent design is important to improve the performance during the stenting process. Stent with good performance in geometric assessment should pass several tests in the unexpanded and expanded condition. The FEM assessment is expected to replace the actual mechanical assessment to save the cost and time of the manufacturing. In this study, the FEM assessment is conducted using the structural nonlinear analyses in ANSYS R15.0. The stent type used in the simulation is the Asymmetric stent and the Sinusoidal stent. The assessments included in this study are the flexibility test on the unexpanded condition (single-load and multi-load) and that on the expanded condition under single point loading. The three-point bending test is chosen as the flexibility test, either for the unexpanded or expanded condition, due to its simplicity. To restrain angular deformation and more save the computation process, a symmetry model (due to longitudinal and angular plane) of each stent type is constructed. By utilizing Multi Point Constraint (MPC) element, the loading is subjected over a pilot node at the center line of the stent. The analysis results showed that Asymmetric stent has lower flexibility comparing with a Sinusoidal stent in the unexpanded configurations. In the case of an Asymmetric stent, its inflated-side is more flexible than the fixed-side.